Psychological impact of single and multiple courses of assisted reproductive treatments in couples: a comparative study - Reis, Salomé (2013)
Objective: To analyze the psychological impact on levels of anxiety and depression in couples who, confronted with the diagnosis of infertility, propose to carry out ART; to evaluate and compare state-trait anxiety and depression levels in couples undergoing ART treatments for the first time and repeatedly, and to verify gender differences. Study design: In this prospective study in the Medically Assisted Reproduction Unit of the Centro Hospitalar de Sao Joao, Porto, Portugal, 89 couples diagnosed with infertility were divided into two groups: (1) couples starting ART for the first time (43), and (2) couples pursuing ART repeatedly (46). Participants completed the Beck Depression Inventory-II (BDI-II) and the State-Trait Anxiety Inventory-Form Y (STAI-Y), prior to their first or subsequent treatment cycle. Results: Couples pursuing ART for the first time show higher levels of state-anxiety compared to couples who repeatedly carry out ART (p < 0.05). Levels of depression are higher in couples who repeatedly carry out ART (p < 0.05). In both study groups, women and men have higher levels of state-anxiety compared to trait-anxiety (p < 0.05). With respect to depression, there are significant differences between genders in both groups, showing higher values in women compared to men (p < 0.01). Conclusions: The results show that there is room to tailor psychological interventions for the specific story of each couple, but we emphasize the importance and need for more studies to support these findings.